Islamic banking selection criteria among kelantanese in Kota Bharu / Farah Adilah Wan Zulkifli - Wan Zulkifli, Farah Adilah (2011)
Nowadays demand for Islamic banking services are increasing among consumers especially for muslims. Therefore, Malaysia has become the first country to implement dual banking in the world. Today we can see that many conventional bank has also implemented their own Islamic banking services in order to compete with the Islamic banking services. Moreover, product services offered by the conventional bank and Islamic bank are slightly the same. But Islamic banking has followed syariah term in order to offer their services. The question here is what criterion that consumers look for in Islamic banking services as their choice rather than conventional bank. The factors affecting customers to select Islamic banking could be the compliance to Islamic Syariah, Convenience, and Cost Benefit.